Mapping the evidence on racialized mothers’ postpartum mental health in Canada: A scoping review protocol - Saima Hirani; Savitha Balachandran; Rubee Dev; Kayoung Lee; Michelle Carter (PLOS One, 2026)
The postpartum period is a time of increased vulnerability to mental health challenges due to physiological, emotional, and social changes, with nearly one-quarter of Canadian mothers reporting symptoms of postpartum depression or anxiety. These challenges may be amplified for racialized mothers, who may encounter systemic barriers such as stigma, discrimination, and limited access to culturally appropriate care. This scoping review aims to map and synthesize the current body of literature on postpartum mental health of racialized mothers living in Canada. This review will be conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for Scoping Reviews (PRISMA-ScR). Two search phases: databases (CINAHL, MEDLINE, PsycINFO and Cochrane Library) and a grey literature search will be used to identify literature. This review will be guided by Arksey and O’Malley’s framework. All studies conducted in Canada and published in English, relevant to postpartum mental health of racialized mothers will be included. The grey literature will focus on programs and interventions for racialized postpartum mothers. We will screen the literature against the inclusion criteria by two independent reviewers and included studies will be presented in a flow diagram in accordance with the PRISMA-ScR guidelines. Data will be extracted and synthesized according to relevant themes or concepts that emerge from the literature and will be presented in diagrammatic or tabular formats. This will be the first scoping review to identify and synthesize evidence on the postpartum mental health of racialized mothers living in Canada. Our results will inform the development of culturally responsive interventions that address the specific needs of this population.